Usability Assessment and Design Proposal for the Web Platform for Curriculum Registration at a Peruvian University - (:unkn) unknown (Springer Nature Switzerland, 2024)
Usability has been recognized as a fundamental element in ensuring the quality of a software. Moreover, the lack of adequate usability can be decisive in the success or failure of the system. This study focuses on the web platform responsible for managin...
Keywords: Usabilidad web; Universidades peruanas